A CRITICAL DISCOURSE ANALYSIS ON ORIFLAME CATALOGUE BEAUTY PRODUCT ADVERTISEMENTS - Mei Lastri E.F. Butar Butar; Anni Holila Pulungan; Rahmad Husein (LINGUISTIK TERAPAN, 2019)
The aims of this study are to investigate linguistic features, to describe the discursive techniques and to describe social implications that are used in oriflame catalogue beauty product advertisements. This research was conducted by using qualitative research design. The data of this study were texts on oriflame beauty product advertisements. The data analyzed by using three dimensional nature of critical analysis as preceded by Fairclough. There are three dimensional frameworks of analysis that are description/ text analysis, interpretation/process and explanation/social. The findings are (1) there were 7 out of 8 kind of linguistic features were found in oriflame catalogue beauty product advertisements. the most dominant linguistic feature used in the advertisement is adjective, (2) there were 9 discursive techniques that found in the second level analysis, the most technique used in the advertisements is emotive word.Keywords: Critical Discourse Analysis, Advertisement, Linguistic Feature, Discursive Technique,  Social Implication